AB0383 EXTREME FATIGUE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND NEUROPSYCHIATRIC SYMPTOMS. (2nd June 2020) - Monahan, R.; Fronczek, R.; Eikenboom, J.; Middelkoop, H.; Beaart- van de Voorde, L. J. J.; Terwindt, G.; Van der Wee, N.; Huizinga, T.; Kloppenburg, M.; Steup-Beekman, G. M.
Abstract : Background: Fatigue is commonly described in chronic illnesses, especially auto-immune disorders such as systemic lupus erythematosus (SLE). Objectives: We aim to study the prevalence of fatigue in SLE patients with NP symptoms and compare fatigue in SLE patients with NP symptoms attributed to major organ involvement due to SLE (NPSLE) with SLE patients with NP symptoms not caused by major nervous system involvement (non-NPSLE). Methods: All patients visiting the tertiary referral center for NPSLE in the LUMC between 2007-2019 with the clinical diagnosis of SLE and age >18 years that signed informed consent were included in this study. Patients underwent a standardized multidisciplinary assessment, including two questionnaires: SF-36 (2007-2019) and multidimensional fatigue index (MFI, 2011-2019). Patients were classified as NPSLE in this study if NP symptoms were attributed to SLE and immunosuppressive or anticoagulant therapy was initiated, otherwise patients were classified as non-NPSLE. The vitality (VT) domain of the SF-36 domain was used to assess fatigue, which generates a score from 0-100, 100 representing the complete absence of fatigue. Patients with a score more than 1 standard deviation (SD) removed from age-related controls of the Dutch general population were classified as fatigued; patients more than 2 SD removed were classified as extremely fatigued 1 . The MFI was also used, which consists of 5 subdomain scores between 0-20, leading to a total score between 0-100, 100 representing the most extreme fatigue. All scores are presented as mean and standard deviation. Results: 373 patients fulfilled the inclusion criteria and SF-36 questionnaires of 328 patients were available (88%). The majority of these patients was female (87%) and 98 were classified as NPSLE (30%). In NPSLE patients, average age was 41 ± 13 years and in non-NPSLE the average age was 45 ± 14 years. The average score of the SF-36 vitality domain was 36.0 ± 20.7 in NPSLE vs 33.9 ± 18.8. in non-NPSLE. Overall, 73.5% of the patients were fatigued and 46.9% extremely fatigued in NPSLE vs 77.8% fatigued and 45.7% extremely fatigued in non-NPSLE. The MFI questionnaire and VAS score were available for 222 patients, of which 65 patients were classified as NPSLE (29.3%). Table 1 depicts the scores of NPSLE and non-NPSLE patients on the MFI subdomains and the VAS score. Conclusion: Nearly half of patients with SLE and NP symptoms are as extremely fatigued as only 2.5% of the general Dutch population. Extreme fatigue is not influenced by major nervous system involvement. References: [1]Aaronson et al. J Clin Epidemiol. Vol. 51, No. 11, pp. 1055–1068, 1998 Disclosure of Interests: Rory Monahan: None declared, Rolf Fronczek: None declared, Jeroen Eikenboom: None declared, Huub Middelkoop: None declared, L.J.J. Beaart- van de Voorde: None declared, Gisela Terwindt: None declared, Nic van der Wee: None declared, Thomas Huizinga Grant/research support from: Ablynx, Bristol-Myers Squibb, Roche, Sanofi, Consultant of: Ablynx, Bristol-Myers Squibb, Roche, Sanofi, Margreet Kloppenburg: None declared, G.M. Steup-Beekman: None declared